Mesenchymal stem cell-derived exosome alleviates sepsis- associated acute liver injury by suppressing MALAT1 through microRNA-26a-5p: an innovative immunopharmacological intervention and therapeutic approach for sepsis - Cai, Jizhen; Tang, Da; Hao, Xiao; Liu, Enyi; Li, Wenbo; Shi, Jian (Frontiers in Immunology, 2023)
Sepsis is a syndrome with disturbed host response to severe infection and is a major health problem worldwide. As the front line of infection defense and drug metabolism, the liver is vulnerable to infection- or drug-induced injury. Acute liver injury (ALI) is thus common in patients with sepsis and is significantly associated with poor prognosis. However, there are still few targeted drugs for the treatment of this syndrome in clinics. Recent studies have reported that mesenchymal stem cells (MSCs) show potential for the treatment of various diseases, while the molecular mechanisms remain incompletely characterized. Herein, we used cecal ligation puncture (CLP) and lipopolysaccharide (LPS) plus D-galactosamine (D-gal) as sepsis-induced ALI models to investigate the roles and mechanisms of mesenchymal stem cells (MSCs) in the treatment of ALI in sepsis. We found that either MSCs or MSC-derived exosome significantly attenuated ALI and consequent death in sepsis. miR‐26a‐5p, a microRNA downregulated in septic mice, was replenished by MSC-derived exosome. Replenishment of miR‐26a‐5p protected against hepatocyte death and liver injury caused by sepsis through targeting Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1), a long non-coding RNA highly presented in hepatocyte and liver under sepsis and inhibiting anti-oxidant system. Taken together, the results of the current study revealed the beneficial effects of MSC, exosome or miR-26a-5p on ALI, and determined the potential mechanisms of ALI induced by sepsis. MALAT1 would be a novel target for drug development in the treatment of this syndrome.